Penerapan Sistem Penjaminan Mutu Pembelajaran PAI - Fuad, Rahmad; Sesmiarni, Zulfani (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
One of the efforts made by the school principal to improve the quality of educational institutions is the implementation of a learning quality assurance system. It is crucial for educational institutions to implement a quality assurance system for Islamic Religious Education (PAI) learning because general schools also need to emphasize religious education. By focusing on this quality assurance system, the goal of improving the quality of education in institutions can be achieved, aligning with the institution's objectives. This research aims to analyze the implementation of the PAI learning quality assurance system in fifth-grade classes at SDN 02 Aur Kuning Bukittinggi. The research method used is descriptive qualitative research with a case study approach. The data collection techniques employed include observation, interviews, document analysis, and reviewing previous studies related to the research topic. The research location is SDN 02 Aur Kuning Bukittinggi. The results indicate that the PAI learning quality assurance system at SDN 02 Aur Kuning Bukittinggi has been effectively implemented through steps such as program planning, the use of appropriate learning media, and regular evaluation of learning outcomes. The PAI curriculum at SDN 02 Aur Kuning Bukittinggi follows an independent curriculum tailored to the students' characteristics and environmental conditions. The implementation of quality assurance in learning adheres to the National Education Standards (SNP) and is supported by supervision and monitoring from the school principal. The evaluation of students' learning outcomes includes daily assessments, periodic tests, midterm exams, and final semester exams.